Treating stable ischemic heart disease with percutaneous coronary intervention - The debate continues - Puri, Rishi; Nicholls, Stephen J. (Cardiovascular Diagnosis and Therapy, 2012)
Nearly 20 ago, Dutch investigators conceptualized a technique of utilizing an intracoronary pressure-sensing guide-wire to evaluate the effect of an epicardial stenosis on myocardial blood flow (1,2), and thus assess the potential of a coronary stenosis to produce ischemia. Throughout the course of the next 15 years, these investigators undertook a number of cleverly designed and well-executed experiments in both animal models of coronary disease (3), and in various human registries (4-8), to validate the concept of fractional flow reserve (FFR). FFR was shown to result in a more selective approach of undertaking percutaneous coronary intervention (PCI), with deferral of PCI for non-ischemic lesions, irrespective of their angiographic severity, found to be safe over the longer term (7).